Activated charcoal hemadsorption in Cerbera odollam poisoning - Dyna Jones; Meenakshi Kalyan; Chaitra Kolli; Hemant Kumar (Apollo Medicine)
Cerbera odollam belongs to the poisonous Apocynaceae family, which grows in coastal salt swamps, creeks and along river banks found in South India. The poisonous part of the plant is the kernel containing the toxin cerberin which is a cardiac glycoside that produces symptoms and signs similar to acute digoxin poisoning. The treatment is mainly symptomatic as well as administration of digoxin immune fab antibodies. Digoxin immune fab antibodies bind with cardiac glycosides to reduce their active concentration. However, there could be various barriers in developing countries in regard to the administration of DigiFab antibodies such as availability and affordability. Activated charcoal, a cheaper alternative, reduces gastrointestinal absorption and enterohepatic recirculation. Although its role in C. odollam poisoning remains unclear, there have been various trials where multidose activated charcoal has been beneficial in glycoside poisoning. We present a case report of a young female with an alleged history of consumption of an unknown plant compound, identified as C. odollam presenting with acute-onset vomiting, altered mental status and laboratory parameters showed hyperkalemia and thrombocytopenia. Electrocardiogram (ECG) showed sinus bradycardia followed by inverted tick mark sign. Serum digoxin levels were raised (4.2 ng/ml). The patient was stabilized with supportive measures and hemadsorption with 300 g of cellulose-coated activated charcoal, which led to the reversal of the ECG and laboratory parameters to normal, leading to the complete recovery of the patient.